THU0248 GLOMERULAR AND TUBULOINTERSTITIAL LESIONS IN PER-PROTOCOL REPEAT BUT NOT BASELINE KIDNEY BIOPSY PORTEND RELAPSE AND LONG-TERM RENAL FUNCTION IMPAIRMENT, RESPECTIVELY, IN INCIDENT CASES OF PROLIFERATIVE LUPUS NEPHRITIS. (2nd June 2020) - Parodis, I.; Adamichou, C.; Aydin, S.; Gomez, A.; Demoulin, N.; Weinmann-Menke, J.; Houssiau, F.; Tamirou, F.
Abstract : Background: In patients with lupus nephritis (LN), clinical response to treatment and renal histopathology have been shown to be discordant. No clinical or laboratory markers have to date been shown to reliably portend renal prognosis, in particular renal function impairment. Objectives: To investigate whether per-protocol repeat renal biopsies are predictive of LN relapses and long-term impairment of renal function. Methods: Forty-two patients with an incident biopsy-proven active proliferative (class III/IV ± V) LN from the LN database of the Université catholique de Louvain were included in the present retrospective study. Per-protocol repeat kidney biopsies were performed in all patients after a median time of 24.3 (IQR: 21.3–26.2) months. The NIH activity index (AI) and chronicity index (CI) scores were assessed in both baseline and repeat biopsies. We defined acute glomerular lesions as cellular proliferation, fibrinoid necrosis or karyorrhexis, cellular crescents, hyaline thrombi or wire loops, and leucocyte infiltration, and chronic glomerular lesions as glomerular sclerosis and fibrous crescents, in alignment with the NIH activity and chronicity indices. Similarly, we defined acute tubulointerstitial lesions as mononuclear cell infiltration and chronic tubulointerstitial lesions as interstitial fibrosis and tubular atrophy. Results: Despite a moderate correlation between urinary protein/creatinine (U-P/C) ratios and AI scores at repeat biopsy (r=0.48; P=0.001), ten patients (23.8%) with U-P/C ratios <1.0 g/g still had a high degree of histological activity (AI score >3). High AI scores in repeat (but not baseline) kidney biopsies were associated with an increased probability and/or shorter time to renal relapse (N=11) following the repeat biopsy (HR: 1.2; 95% CI: 1.1–1.3; P=0.007), independently of proteinuria levels. This association remained significant for the NIH activity index items within the glomerular but not the tubulointerstitial compartment of the kidney biopsies. High NIH CI scores in repeat (but not baseline) kidney biopsies were associated with a sustained increase in serum creatinine levels corresponding to ≥120% of the baseline value (HR: 1.8; 95% CI: 1.1–2.9; P=0.016) through a median follow-up time of 131.5 (IQR: 73.8–178.2) months, being the case also for acute and chronic tubulointerstitial lesions in repeat but not baseline kidney biopsies. Conclusion: Our results highlight the usefulness of per-protocol repeat biopsies as an integral part of the treatment evaluation, also in patients who have shown adequate clinical response. Glomerular lesions consistent with active renal disease portend LN relapses, while tubulointerstitial lesions consistent with active disease and chronic damage portent long-term renal function impairment. Disclosure of Interests: Ioannis Parodis: None declared, Christina Adamichou: None declared, Selda Aydin: None declared, Alvaro Gomez: None declared, Nathalie Demoulin: None declared, Julia Weinmann-Menke: None declared, Frederic Houssiau Grant/research support from: UCB, Consultant of: GSK, Farah Tamirou: None declared